DYNAMIC ANALYSIS OF MATHEMATICAL MODEL OF GLUCOSE, INSULIN CONCENTRATION, AND BETA SELECT CYCLES OF DIABETES MELLITUS DISEASE - Luailiyah, Siti Zahirotul; Pagalay, Usman; Alisah, Evawati; Kusumastuti, Ari (Proceedings of the International Conference on Green Technology, 2017)
This study examines the relationship between the components of glucose , insulin  and beta cells (  in the body by looking at the genetic predisposition ( ). The three components are very important for the body. The body requires glucose from food which is then converted into energy and partially stored in muscle or liver. Excess glucose in the blood will be balanced by insulin from beta cells in the pancreas. The focus studied is the dynamic analysis of the three components. The benefit of this research is know the stability behavior for glucose, insulin and beta cells. The results of this study obtained an equilibrium point consisting of three things: the point of pathological equilibrium, susceptible to disease and physiological. And stability analysis is consist of stable and unstable. And the behavior of glucose, insulin and beta cells of the model can be known through phase and simulation fields. For further research is expected to analyze the model by changing the initial value.